Factors Influencing Students' Interest in Investing in the Sharia Capital Market: A Case Study on Students of Mataram University - Pratama, Muhammad Alfi Satia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The growing enthusiasm of the predominantly Muslim Indonesian population for investing, one of the largest in the world, has led to the emergence of the sharia capital market as a significant economic movement that adheres to Islamic values. This study aims to understand the interest of students in investing in the sharia capital market with the dependent variables being motivation, investment knowledge, minimum investment capital, risk perception, return, and religiosity. This research is quantitative. The data source used in this study is primary data obtained from distributing questionnaires offline to respondents, namely students. The sample criteria in this study are active D3, S1, and S2 students at Mataram University. The research was conducted by distributing questionnaires. Questionnaires were distributed to 61 samples. The study shows that the variables of motivation, investment knowledge, minimum investment capital, risk perception, return, and religiosity do not influence students' interest in investing in the sharia capital market.